Clinical outcomes in patients with a diagnosis of “indefinite for dysplasia” in Barrett’s esophagus: a multicenter cohort study - Sinh, Preetika; Anaparthy, Rajeswari; Young, Patrick E.; Gaddam, Srinivas; Thota, Prashanthi; Balasubramanian, Gokulakrishnan; Singh, Mandeep; Higbee, April D.; Wani, Sachin; Gupta, Neil; Rastogi, Amit; Mathur, Sharad C.; Bansal, Ajay; Horwhat, John D.; Cash, Brooks D.; Falk, Gary W.; Lieberman, David A.; Vargo, John J.; Sampliner, Richard E.; Sharma, Prateek (Endoscopy, 2015)
Background and study aim: Data are limited on the natural history of patients with Barrett’s esophagus with a diagnosis of “indefinite for dysplasia” (IND). The aims of this study were to: (i) determine rates of progression to high grade dysplasia (HGD) or esophageal adenocarcinoma, and compare these with rates for low grade dysplasia (LGD); and (ii) determine the proportion of patients whose histological IND diagnosis changed on follow-up endoscopy.Patients and methods: Demographic, endoscopic, and histologic information of patients with diagnoses of IND and LGD and at least 12 months of follow-up were extracted from the database of a multicenter Barrett’s esophagus study. Rates and times for progression to HGD and esophageal adenocarcinoma and regression to nondysplastic epithelium were calculated. Proportions of diagnoses upgraded to HGD/esophageal adenocarcinoma or downgraded to nondysplastic epithelium at first follow-up endoscopy were evaluated. Results: Amongst 2264 patients, 83 with a diagnosis of IND (mean age 60 years, 95 % men, 95 % white; mean follow-up 5.6 years) and 79 with diagnosis of LGD were identified. In the IND group, annual incidences of esophageal adenocarcinoma and HGD were 0.21 % and 0.64 %, respectively, representing a combined incidence of 0.8 %. Mean time to progression was 4.72 years. Within the IND group 55 % patients showed regression to nondysplastic epithelium at first follow-up endoscopy and the overall regression rate was 80 %. Corresponding rates in LGD patients were similar.Conclusions: Lesions diagnosed as IND and LGD show similar biological behavior and can be treated as a single category with respect to surveillance and follow-up.